An equilibrium and kinetic study for the removal of reactive red M5B using phosphoric acid treated activated carbon. (16th April 2020) - Selvan, K. Senthamil; Sundari, P. Meena; Madhavan, S.; Palanivel, M.; Jayakumar, R.
The objective of the study is to develop an adsorbent which is abundant with economical and environmental friendly characteristics to remove reactive dye from its aqueous solution. The municipal solid waste modified by H3 PO4 activated carbon (MSWAC) was prepared and characterised. The adsorption capacity of the activated carbon was tested towards reactive red M5B (RR), a representative of industrial effluent at varied operational conditions by using batch method. Langmuir, Freundlich and Temkin adsorption isotherm models were applied to describe the characteristics of adsorption behaviour. Kinetic data were fitted to pseudo-first-order, pseudo-second-order and intra-particle diffusion models. The virgin characteristics of MSWAC were studied using BET surface area, scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) studies. The result indicated that MSWAC as a low cost adsorbent and it can be effectively used for treating textile industry effluent.